Adult dynamic heart evaluated by the proportions of entropy - Rodríguez Velásquez, Javier; Prieto, Signed; Ramírez López, Leonardo (Universidad y Salud, 2017)
Introduction: A new mathematical methodology of clinical application has been developed from the theory of dynamic systems, together with the theory of probability and the concept of entropy. Objective: To apply the methodology previously developed to evaluate the heart dynamics of adult through the probability and proportions of entropy of the attractor. Materials and methods: A blind study was developed taking as Gold Standard the conventional diagnosis issued by an expert with 480 Holter, 30 normal dynamics and 450 with different pathologies. For each Holter, a numerical attractor was generated by quantifying the probability of appearance of consecutive pairs of cardiac frequencies, subsequently evaluating entropy, S/K ratio and proportions for each dynamic for at least 18 hours. The values of sensitivity, specificity and Kappa coefficient were found. Results: The applied methodology allowed to differentiate quantitatively normality of disease, finding the values of the proportions in the established ranges. The sensitivity and specificity values were 100%, and Kappa coefficient was 1. Conclusion: It is possible to diagnose cardiac dynamics for at least 18 hours based on the probability distributions of the appearance of consecutive pairs of cardiac frequencies and their entropy.